Pengaruh Pembelajaran Berbasis E-learning Terhadap Hasil dan Kemandirian Belajar Siswa Kelas X MAN 3 Aceh Timur - Sari, Nindian (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
The purpose of the study was how the Effect of E-learning-Based Learning on Learning Outcomes and Independence of Class X MAN 3 East Aceh Students. This research uses quantitative research using experimental research methods. The design used in this study is a one group pretest-posttest design, this design is used for one group of experimental subjects only. The results of the research and evidence show that there is a significant effect between the initial test scores and the final test scores in class X-MIA.1 and X-MIA.2 on mathematical logic material. The results of the post-test evaluation of the experimental class found that the average learning outcomes of 67.50 students' scores had increased in all students, judging from the post-test scores of the experimental class of 53.44, there was a control that increased the effect of e-learning by 26.31%, this shows that there is a significant effect. significant effect on student learning outcomes of MAN 3 East Aceh. The e-learning method in its application makes students more active and creative in terms of obtaining material sources and more independent discussion, while the teacher only directs and guides students. With the e-learning method, students in learning activities will be more flexible and creative in finding solutions to the material discussed. The e-learning method plays a very active role in disseminating material and understanding the material more deeply, so that the selection of this method is one of the appropriate learning methods in the learning process, but this method must be supported by the willingness of students, be serious, and must be accompanied by the basic abilities of students. using internet facilities, in this case the teacher gives directions to visit the blogspot address and the intended email.